Inhibition of DNA damage response at telomeres improves the detrimental phenotypes of Hutchinson–Gilford Progeria Syndrome - Julio Aguado (Nature Portfolio, 2019)
Hutchinson–Gilford progeria syndrome causes premature aging. Here the authors show that activation of the DNA damage response at dysfunctional telomeres and transcription of telomeric non-coding RNAs contributes to the pathogenesis, which can be ameliorated by treatment with sequence-specific telomeric antisense oligonucleotides.